2011
DOI: 10.1021/ie101921y
|View full text |Cite
|
Sign up to set email alerts
|

Facility Location and Supply Chain Optimization for a Biorefinery

Abstract: This paper presents a systematic approach for the optimal production planning and facility placement of a biorefinery. A structural representation is first developed to include sources of biomass feedstock, distributed preprocessing hubs, and centralized processing facilities to produce desired products and byproducts. An optimization formulation is developed to determine the optimal supply chain, size, operational strategies, and location of the biorefinery and preprocessing hub facilities. The model consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(98 citation statements)
references
References 30 publications
0
95
0
Order By: Relevance
“…[b] Relative cost (per input BDMT of input feedstock) of an additional $.10/kWh paid for electricity. variables to trigger costs by scale or configuration (Bowling et al, 2011;Rodriguez et al, 2016). The mathematical model uses biochar as its example product due to recent high interest in the potential U.S. biochar market which is estimated to reach $5 billion/year in the near term (Delaney, 2015) with speculation that wholesale price at commercial production levels would be near $1650/tonne ($1,500 per ton) (Biofuels Digest, 2017).…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[b] Relative cost (per input BDMT of input feedstock) of an additional $.10/kWh paid for electricity. variables to trigger costs by scale or configuration (Bowling et al, 2011;Rodriguez et al, 2016). The mathematical model uses biochar as its example product due to recent high interest in the potential U.S. biochar market which is estimated to reach $5 billion/year in the near term (Delaney, 2015) with speculation that wholesale price at commercial production levels would be near $1650/tonne ($1,500 per ton) (Biofuels Digest, 2017).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The concept of facility location is a mature science that has incorporated objective functions ranging from minimizing overall setup cost, minimizing time/distance traveled, minimizing number of located facilities to maximizing service or responsiveness (Farahani et al, 2010). In particular, there have been significant contributions in biorefinery placement and supply chain product production incorporating many of these same elements as well as economies of scale (Bowling et al, 2011). However, the pairing of optimized and detailed system logistics coupled with transportable scale design evaluating mobility and scale economic tradeoffs has not yet been studied.…”
mentioning
confidence: 99%
“…Increasingly, however, alternative product streams are being considered, and as biorefining for non-biofuel purposes become more inevitable, tools to evaluate the economic viability of various options are increasingly needed. Previous supply and/or value chain related research efforts have focussed on ethanol production via lignocellulose with specific targets on the distribution of processing hubs [2], comparison of biomass sources [3,4], first and second generation bioethanol technology assessments [5], weather uncertainties [6] and feedstock properties such as moisture content [7]. In addition, transport cost and distance were demonstrated to be an important consideration for biofuel supply chain networks [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Murillo-Alvarado et al (2013) reported an optimization approach that determines the optimal supply chain for biorefineries in Mexico while maximizing profits and minimizing emissions of greenhouse gases and considering supply and demand. Bowling et al (2011) addressed the planning for the optimal production of a distributed refinery system involving the optimal selection for the location, raw materials, and pre-processing and processing facilities. ElHalwagi (2016a) introduced a sustainability-weighted economic metric to couple economic and other sustainability objectives.…”
Section: Introductionmentioning
confidence: 99%